“I STILL WANT TO KNOW THEY’RE NOT TERRIBLE PEOPLE”: NEGOTIATING TRUST, PLEASURE AND QUEER ETHICS IN LGBTQ+ YOUNG PEOPLE’S DATING APP USE - Pym, Tinonee; Albury, Kath; Byron, Paul; McCosker , Anthony; Race, Kane (AoIR Selected Papers of Internet Research, 2019)
Dating and hook-up apps constitute spaces of intense negotiation around issues of sex, identity and intimacy, in which norms are tested and reinforced. This paper examines discussions of ‘ideal app use’ which emerged in qualitative workshops conducted in 2018 with 23 LGBTQ+ app-users aged 18-35 in urban and regional New South Wales. We explore how a reading of in-app practices - such as messaging, picture-sharing and blocking - through a lens of queer ethics can inform LGBTQ+ young people’s ‘rules’ for app use. Participants were invited to create ’how-tos’ for ideal app use, and describe the ways they distinguished ‘good’ (or trustworthy) profiles from ‘bad’ (untrustworthy) profiles via creative design activities. In their discussions, participants articulated their ‘rules’ for filtering matches in relation to particular design features of apps which enabled (sexed and gendered) cultures of accountability to others. As in Duguay’s (2017) research on queer women’s deployment of in-app affordances as ‘identity modulation’, participants interacted with other users and interpreted their profiles in relation not only to sexual desires, but also queer politics and identity. In many instances, this was expressed through a heightened sense of responsibility for self-knowledge and self-disclosure, and a need to connect with ‘good people’ with a shared political sensibility. At other times, participants acknowledged the challenges of negotiating politicised responsibility to others while simultaneously pursuing the kinds of pleasurable connections they sought on apps, and limiting their own self-disclosure as a means of guarding their physical and emotional safety.